Bagaimana Mempersiapkan HOTS untuk menghadapi Abad ke-21 - Jihannita Jihannita; Zuhdan Kun Prasetyo; Insih Wilujeng (Jurnal Penelitian Pendidikan IPA, 2023)
Higher-order thinking skills (HOTS) have become a focus in the goal of providing education in Indonesia. The purpose of this study is to analyze the extent to which research that seeks HOTS in Indonesia is developed especially in relation to facing the 21st century, at present. The analysis is carried out on articles published nationally and internationally. The analysis was conducted on 26 articles indexed by SINTA and DOAJ. The findings show that research on higher-order thinking skills (HOTS) in Indonesia is dominated by the development of instruments used to measure students' HOTS as well as the application of learning using innovative methods to improve HOTS. Scientific disciplines developed on the basis of higher-order thinking skills are also very diverse with students in universities as a sample that is often used. HOTS is defined as based on the notion of a problem-solving thinking framework, Bloom's cognitive domain and its revisions, and HOTS Climate Change which emphasizes the level of innovation development. Most sample sizes are in the range of 50-100 samples. The most frequently used research design is RnD research